Analysis of the Role of Instagram as a Public Communication Medium: A Case Study of the Public Relations Division of Polresta Cirebon in Building Public Trust - Ayunda Ganesha Gita; Tasya Nabila Fauzi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This study examines the role of the Cirebon Police Public Relations Department in building public trust through the use of social media, particularly Instagram, as a means of public communication in the digital era. The research background is based on the importance of public trust in the police institution in carrying out its duties. Using the communication management theory of Cultip, Centre, and Broom, this study examines four stages of communication: problem identification, planning, implementation, and evaluation. The research method used was descriptive qualitative, with data collected through observation, documentation, and interviews, and analyzed using the Miles and Huberman model. The results show that the Cirebon Police Public Relations Department consistently utilizes Instagram as a two-way interactive medium to convey information, educate the public, correct hoaxes, and build a positive image. Content such as the "Friday Curhat" program, morning roll call, and night patrols serve as strategic tools for creating transparency, participation, and emotional closeness with the community. Public sentiment analysis showed a majority of responses were positive (80%), neutral (20%), and no negative comments, indicating the success of this communication strategy in strengthening public trust. This research confirms that integrating social media with communication management strategies can support the effectiveness of police duties and enhance the institution's legitimacy in the eyes of the public.